Modulaciones teológicas del tiempo. Ensayo sobre las formas de duración según la teología - Uríbarri Bilbao, Gabino (Estudios eclesiásticos, 2006)
This essay asks whether the divine eternity, as a characteristic type of duration, is modulated throughout the History of Salvation by divine implication in creation, incarnation and resurrection of the humanity in Christ. Also investigated is how the duration of human beings is modulated by their relationship to God: in Paradise, after the Fall, after salvation in Christ, and in the final consummation. As a result, several different modulations of time are proposed. Some are primal: eternity (God) and sequentiality (creature); once these two come into relationship they bear some more complex others: eternity being capable of sequentiality, eschatological sequentiality, pre-Adamic time, Adamic time, the Christian eon, eschatological time, sacramental time, pneumatological time, historical time.